2018
DOI: 10.7196/samj.2018.v108i6.12913
|View full text |Cite
|
Sign up to set email alerts
|

Economic evaluation of safety-engineered devices and training in reducing needlestick injuries among healthcare workers in South Africa

Abstract: A combination strategy in which both SEDs and a TP are adopted is preferred.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 41 publications
0
8
0
2
Order By: Relevance
“…Korea and the United States have included care homes as a priority group for diagnostic testing (OECD, 2020 [207]; OECD, 2021 Forthcoming [208]). 3…”
Section: Countries Have Taken Steps To Limit the Spread Of Covid-19 In Ltcmentioning
confidence: 99%
See 1 more Smart Citation
“…Korea and the United States have included care homes as a priority group for diagnostic testing (OECD, 2020 [207]; OECD, 2021 Forthcoming [208]). 3…”
Section: Countries Have Taken Steps To Limit the Spread Of Covid-19 In Ltcmentioning
confidence: 99%
“…Patient safety and quality of care continue to be a global policy priority, with a series of recent international reports highlighting the extent of patient harm, its health and economic consequences, and the comparatively modest investment needed to improve the situation (Slawomirski, Auraaen and Klazinga, 2017 [1]; Slawomirski, Auraaen and Klazinga, 2018 [2]; de Bienassis, Llena-Nozal and Klazinga, 2020 [3]). However, patients are not the only ones who may experience harm in a health system.…”
mentioning
confidence: 99%
“…The difficulties observed in the institutional documents point to the need to adjust the SSD purchase time with training in order to improve cost-effectiveness. Allowing the SSDs to be made available for use, prior to training, can contribute to an increase in the number of accidents and to a lower cost-effectiveness ratio of the SSDs (11,19) .…”
Section: Readingmentioning
confidence: 99%
“…International studies with characteristics similar to the PPAMP, through robust statistical analyses, have shown that the program's efficiency concerns the PCMs, responsible for reducing the frequency of accidents (10)(11)19) .…”
Section: Readingmentioning
confidence: 99%
“…Despite the recommendations, the identified articles (Table 1) show a variation in analysis structure in terms of perspective, time horizon and data source. None of the studies describe in detail the structure of their economic model except De Jager (2018) [8], who developed a Markov simulation model with one-year cycle and seven health states over 45 years. All studies take the number of NSIs from spontaneous reporting systems, either via retrospective review of reports, prospective collection of data from reports, or a summary of reports found in literature.…”
Section: Model Structurementioning
confidence: 99%